Front-end tooling with Gulp, Bower, and Yeoman - Baumgartner, Stefan (Manning Publications, 2017)
FrontEnd Tooling with Gulp, Bower, and Yeoman teaches you how to use and combine these popular tools to set up a customized development workflow from start to finish. About the Technology In large web dev projects, productivity is all about workflow. Great workflow requires tools like Gulp, Bower, and Yeoman that can help you automate the design-build-deploy pipeline. Together, the Yeoman scaffolding tool, Bower dependency manager, and Gulp automation build system radically shorten the time it takes to release web applications. About the Book Front-End Tooling with Gulp, Bower, and Yeoman teaches you how to set up an automated development workflow. You'll start by understanding the big picture of the development process. Then, using patterns and examples, this in-depth book guides you through building a product delivery pipeline using Gulp, Bower, and Yeoman. When you're done, you'll have an intimate understanding of the web development process and the skills you need to create a powerful, customized workflow using these best-of-breed tools. What's Inside Mastering web dev workflow patterns Automating the product delivery pipeline Creating custom workflows About the Reader This book is suitable for front-end developers with JavaScript experience. About the Author Stefan Baumgartner has led front-end teams working across a wide range of development styles and application domains.